E-house rental service: a business model for UiTM Shah Alam / Junainah Tolani - Tolani, Junainah (2005)
Nowadays, the uses Internet become more important to all people around the world. Through the Internet, there are many services offered to a public such as online reservation ticket, buying and selling goods and services, advertisement goods and services, etc. House rental services is a services that been offer by the landlords to a house tenants that look out for a house rent. In UiTM Shah Alam, they provide this kind of services to their students that look out for a house rent. Through a manual method, by putting advertisement of house rent at HEP Bulletin Board, college and logbooks. And with the proposed of electronic house rental services (e-HRS) it will help dissemination rental unit information widely through an online services. This research studied on the perception of a landlords and UiTM Students towards the proposed of electronic house rental services (e HRS). As a result, landlords and UiTM students can use e-HRS as another alternative to get rental unit information.